2001
DOI: 10.1007/s004050000302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different 3D navigation systems by a clinical "user"

Abstract: Three-dimensional navigation systems are routinely used in endoscopic skull base surgery, neurosurgery, maxillo-facial and endoscopic sinus surgery. Their precision can, however, change in the course of one experiment. We have compared five different 3D navigation systems and discuss here possible reasons for the limits of system precision. A plexiglass cube on which test points were marked served as a test-model. Two well-trained system users measured the distances between the test points in each of the five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Electromagnetic (EM) tracking measures the magnetic field between a transmitter attached to the US probe and a receiver. Limitations of optical systems are mainly the requirement of a constant line of sight (Cartellieri et al, 2001;Rousseau, 2003), and those of EM sensors are errors induced by metallic object interference and a variable performance depending on the scanning distance (Birkfellner et al, 1998a,b;Frantz et al, 2003;Rousseau, 2003). Additionally, uneven volume sampling generated by the 3D-US freehand tracking method adds uncertainty to the reconstruction.…”
Section: Introductionmentioning
confidence: 98%
“…Electromagnetic (EM) tracking measures the magnetic field between a transmitter attached to the US probe and a receiver. Limitations of optical systems are mainly the requirement of a constant line of sight (Cartellieri et al, 2001;Rousseau, 2003), and those of EM sensors are errors induced by metallic object interference and a variable performance depending on the scanning distance (Birkfellner et al, 1998a,b;Frantz et al, 2003;Rousseau, 2003). Additionally, uneven volume sampling generated by the 3D-US freehand tracking method adds uncertainty to the reconstruction.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, navigation systems have been widely used in various surgical fields, especially in neurosurgery, otorhinolaryngologic surgery, and spinal surgery [6][7][8]. Since laparoscopic surgery essentially involves monitor-based surgery, monitor-based augmented reality (AR) visualization can be naturally integrated into it.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore common practice to estimate the system's overall accuracy in a controlled laboratory setting using precisely built phantoms. [21][22][23] To make a conclusion on the potential clinical accuracy, the differences between the clinical and laboratory settings must be carefully examined.…”
Section: Introductionmentioning
confidence: 99%
“…6,[21][22][23][24][25] Although much has been written about conventional neuronavigation systems, the literature on accuracy measurements of ultrasound-based neuronavigation is sparse. Hata et al 4 reported a root-mean-square (RMS) error of 3.1 mm, with standard deviation 2.5 mm, at a depth of 10 mm from the transducer.…”
Section: Introductionmentioning
confidence: 99%